Contemporary Issues and Challenge in Early Childhood Education in the Asia-Pacific Region edited by Minyi Li, Jillian Fox, Susan Grieshaber. - Li, Minyi.; Li, Minyi.; Fox, Jillian.; Fox, Jillian.; Grieshaber, Susan.; Grieshaber, Susan. (New Frontiers of Educational Research, 2017)
This book investigates the unique and dynamic approaches to key issues of changing images of child and childhood, by different countries in the Asia-Pacific. Key concepts considered are re-conceptualizing early childhood education and care, re-eaxming early learning standards and redefining professionalism. The Asia Pacific region includes countries belonging to both the Majority and Minority worlds and which vary widely in terms of their cultural geography, social-cultural beliefs, and levels of development, demographic profiles, political systems and government commitments to early childhood services. An international team of experienced researchers from different countries guarantees diverse perspectives. By examining different countries’ policy choices and evidence-based practices, the authors show how best to provide for young children based on their countries’ strategies.